Efeito agudo da fototerapia por meio de diodos emissores de luz (LED) na cinética do consumo de oxigênio pulmonar, desoxigenação muscular e na resposta de glicemia e lactacidemia em homens com diabetes mellitus e saudáveis - Francisco, Cristina de Oliveira (2016)
Type 2 diabetes mellitus (DM) is responsible for quality of life reduction due its negative impact in the physical exercise capacity. The impairment of cardiopulmonary fitness and lower values in oxygen uptake in exercise tests has been associated with factors related with diabetes complications. Phototherapy is a resource largely utilized due it action in biological systems and it may be adjuvant to exercise to improve muscular efficiency and increase aerobic capacity. Thus, the question if this resource may be benefit to populations with DM. Therefore, we proposed a study protocol randomized, double-blind, placebo controlled to evaluate the acute effect of light emitting diode (LED) in cardiorespiratory and hemodynamic adjustments of moderate exercise in cycloergometer, as well as, in lactate and glucose levels pre and post intervention and after exercise in men aged between 45 and 64 years, with DM and health. Then, two studies were performed. In the study 1 it was evaluated the acute effect of phototherapy (LED-150J) in two groups: DM group (DMG) and health group (HG) (n=16 and n=9, respectively). The groups were paired by age and body mass index. The LED reduced significantly the glucose levels in DMG after exercise and do not affect the lactate levels, cardiorespiratory and hemodynamic adjustments of aerobic exercise in both groups. Our results suggest that LED in combination with moderate exercise decrease acutely the glucose levels in adult subjects with DM. The study 2 aimed evaluate the acute effect of two different doses of phototherapy. Participated in this study two groups of men with DM: LED-150J (n=16) and LED-300J (n=17). The LED-150J reduced the levels of glucose after exercise. The LED-300J increased the lactate levels after exercise in effective session compared with placebo. Any doses changed the cardiorespiratory and hemodynamic adjustments. This study demonstrated that the phototherapy with LED using the 300J dose did not improved the parameters studied and the 150J dose improved the glycaemia and should be used in combination with other therapies for the hyperglycemia management in individuals with DM. The general conclusion of this thesis is that our findings suggest that phototherapy associated with moderate physical exercise have therapeutic potential to control glycaemia in DM, however, further studies should be conducted investigating the dose window and dose-response capable to change acutely the cardiopulmonary and hemodynamic adjustments and lactate levels.